Pedro Pino : governor of Zuni Pueblo, 1830-1878 - Hart, E. Richard (Utah State University Press, 2003)
"Pedro Pino, or Lai-iu-ah-tsai-lu (his Zuni name) was for many years the most important Zuni political leader. He served during a period of tremendous change and challenges for his people. Born in 1788, captured by Navajos in his teens, he was sold into a New Mexican household, where he obtained his Spanish name. When he returned to Zuni, he spoke three languages and brought with him a wealth of knowledge regarding the world outside the pueblo. For decades he ably conducted Zuni foreign relations, defending the pueblo's sovereignty and lands, establishing trade relationships, interacting with foreigners-from prominent military and scientific expeditions to common emigrants-and documenting all in a remarkable archive. Steeped in Zuni traditions, he was known among other things for his diplomatic savvy, as a great warrior, for his oratory, and for his honesty and hospitality. More than a biography, Richard Hart's work provides a history of Zuni during an especially significant period."--Publisher's description